Urgensi Adab Membaca Al-Qur’an dan Berdoa dalam Membangun Kesalehan Individual dan Sosial - Luluk Khoiriyah; Wina Diah; Ahmad Asrin (Prodi Pendidikan Keagamaan Islam, 2025)
This study aims to examine the meaning and urgency of the ethics (adab) of reciting the Qur'an and supplication (du'a) in an effort to cultivate individual and social piety among Muslims. Reciting the Qur'an and praying are not merely ritualistic activities but also serve as instruments for spiritual education that foster awareness, proximity, and submission to Allah SWT. The ethics within these two practices serve as a vital foundation to ensure that worship does not lose its ethical and spiritual essence. Employing a qualitative-descriptive approach through the study of classical and contemporary Islamic literature, this paper explores the theological, psychological, and social dimensions of Qur'anic recitation and supplication. The findings indicate that the ethics of reciting the Qur'an such as maintaining purity, tartil (measured recitation), and tadabbur (reflection) cultivate inner peace and enhance the understanding of Islamic teachings. Meanwhile, ethics in supplication such as sincerity, humility (khusyu'), and modesty strengthen the individual's spiritual relationship with God and foster empathy toward others. Consequently, the understanding and application of ethics in reciting the Qur'an and supplication not only implicate personal piety but also impact the formation of social behaviors that are harmonious, polite, and civilized. This study reinforces that the internalization of ethical values in religious life is a strategic step toward building a Muslim society that is characterized by integrity, morality, and a focus on divine values.